2012
DOI: 10.1103/physrevb.86.104510
|View full text |Cite
|
Sign up to set email alerts
|

Magnetization in the superconducting state of UPt3from polarized neutron diffraction

Abstract: The heavy-fermion superconductor UPt3 is thought to have odd parity, a state for which the temperature dependence of the spin susceptibility is an important signature. In order to address conflicting reports from two different experiments, the NMR Knight shift and measurements of the anisotropy of the upper critical field, we have measured the bulk susceptibility in a high-quality single crystal using polarized neutron diffraction. A temperature-independent susceptibility was observed for H||a through the tran… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 30 publications
2
13
0
Order By: Relevance
“…In previous work we measured the magnetic susceptibility with H ⊥ c using polarized neutron scattering for a UPt 3 crystal with high purity, residual resistance ratio (RRR) of 600 and mass 15 g. 36 We found that the spin susceptibility is temperature independent in the superconducting state for this orientation consistent with Knight shift results. 10,11 Here we extend these measurements for H||c with a smaller crystal, 0.4 g, of even higher purity grown at Northwestern University (RRR = 900), 18 for which a strong temperature dependence of the susceptibility is expected from the E 2u theory for odd-parity superconductivity with angular momentum locked to the c-axis.…”
supporting
confidence: 75%
See 2 more Smart Citations
“…In previous work we measured the magnetic susceptibility with H ⊥ c using polarized neutron scattering for a UPt 3 crystal with high purity, residual resistance ratio (RRR) of 600 and mass 15 g. 36 We found that the spin susceptibility is temperature independent in the superconducting state for this orientation consistent with Knight shift results. 10,11 Here we extend these measurements for H||c with a smaller crystal, 0.4 g, of even higher purity grown at Northwestern University (RRR = 900), 18 for which a strong temperature dependence of the susceptibility is expected from the E 2u theory for odd-parity superconductivity with angular momentum locked to the c-axis.…”
supporting
confidence: 75%
“…In Fig. 4(a), reproduced from our earlier work, 36 we show the complete temperature dependence of the susceptibility from neutron scattering at 1.0 T along our SQUID measurements including earlier susceptibility measurements from Frings et. al.…”
mentioning
confidence: 54%
See 1 more Smart Citation
“…Our sample consists of a high-quality, 15 g single crystal (RRR > 600), cut into two pieces, and is described by Gannon et al [20]. The UPt 3 crystals were co-aligned, fixed with silver epoxy to a copper cold finger, and mounted to the mixing chamber of a dilution refrigerator with the crystal a-axis vertical and the c and a * -axes in the horizontal plane.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…A number of experimental observations are consistent with E 2u pairing symmetry. Muon and 195 Pt Knight shift studies [58,59], as well as polarized neutron diffraction measurements [60], suggest spin-triplet pairing with parallel spins in the ab-plane. Direction-dependent thermal conductivity [61,62], Josephson interferometry [63,64], and vortex lattice [65,66] model of the order parameter [67].…”
Section: Cecoinmentioning
confidence: 95%